This Book Is Not Good For You - Bosch, Pseudonymous; Ford, Gilbert (New York : Little, Brown, 2009)
As an evil dessert chef concocts a recipe for disaster in the form of a tempting chocolate bar, Cass and Max-Ernest attempt to stop an evil organization from carrying out its plot to gain immortality and wreak havoc on the world.
Keywords: Desserts -- Fiction; Immortality -- Fiction; Fiction